Extent and characterisation of salt-affected soils in Iran and strategies for their amelioration and management - Qadir, Manzoor; Qureshi, Asad Sarwar; Cheraghi, S.A.M. (2008)
Salinisation of land resources is a major impediment to their optimal utilisation in many arid and semi-arid regions of the world including Iran. Estimates suggest that about 34 million ha, including 41 million ha of the irrigated land, are salt-affected in Iran as the consequence of naturally occurring phenomena and anthropogenic activities. The annual economic losses due to salinisation in the country are more than US$ 1 billion. With variable levels of success, different approaches?salt leaching and drainage interventions, crop-based management, chemical amendments and fertilisers and integrated application of these approaches?have been used to enhance the productivity of salt-affected soils in the Country. From sustainable management perspective, it is revealed from the past research that integrated salinity management and mitigation approaches have the potential to successfully address the complex problems of salt-induced land degradation in Iran. As the growing need to produce more food and fibre for the expanding Iranian population necessitates the increased use of salt-affected land resources in the foreseeable future, there is an urgent need to develop and implement a pertinent National Strategic Plan. In addition to establishing networks for monitoring spatial and temporal changes in soil salinity and water quality, this plan should integrate the management of salt-affected environments into the overall management of land and water resources in the country. It should also address different management aspects of salt-affected land resources in a holistic manner by considering the biophysical and environmental conditions of the target areas as well as livelihoods of the affected communities. The involvement of the communities will facilitate in developing a greater understanding about the potential uses and markets of the agricultural products produced from salt-affected areas.